THE VIEWS OF EASTERN THINKERS ABOUT GENDER EQUAL RELATIONS IN THE FAMILY (Conferencea, 2023)
This article is about the opinion of Eastern thinkers on the issues of gender equality in family relations, the culture of interpersonal relations in the family, child upbringing, the relationship between men and women, and the formation of human qualities is expressed.